The Patient’s Guide to Psoriasis Treatment. Part 2: PUVA Phototherapy - Farahnik, Benjamin (Dermatol Ther (Heidelb), 2016)
BACKGROUND: PUVA treatment is photochemotherapy for psoriasis that combines psoralen with UVA radiation. Although PUVA is a very effective treatment option for psoriasis, there is an absence of patient resources explaining and demonstrating the process of PUVA. Studies have shown that patients who viewed videos explaining the treatment procedures for various medical conditions had a greater understanding of their treatment and were more active participants in their health. OBJECTIVE: To present a freely available online guide and video on PUVA treatment designed for patient education on PUVA. METHODS: The PUVA treatment protocol used at the University of California—San Francisco Psoriasis and Skin Treatment Center as well as available information from the literature was reviewed to design a comprehensive guide for patients receiving PUVA treatment. RESULTS: We created a printable guide and video resource that reviews the benefits and risks of PUVA, discusses the three types of PUVA (hand–foot soak, full body soak, and systemic), demonstrates the PUVA process, and provides practical tips for safe use. CONCLUSION: Online media and video delivers material in a way that is flexible and often familiar to patients. This new format is beneficial for prospective patients planning to undergo PUVA treatment, health-care providers, and trainees who want to learn more about this treatment.